The Potential Role of Cyclopeptides from Pseudostellaria heterophylla, Linum usitatissimum and Drymaria diandra, and Peptides Derived from Heterophyllin B as Dipeptidyl Peptidase IV Inhibitors for the Treatment of Type 2 Diabetes: An In Silico Study - Hui-Jun Liao; Jason T. C. Tzen (Metabolites, 2022)
Dipeptidyl peptidase 4 (DPP4) inhibitors can treat type 2 diabetes by slowing GLP-1 degradation to increase insulin secretion. Studies have reported that Pseudostellaria heterophylla, Linum usita-tissimum (flaxseed), and Drymaria diandra, plants rich in Caryophyllaceae-type cyclopeptides and commonly used as herbal or dietary supplements, are effective in controlling blood sugar. The active site of DPP4 is in a cavity large enough to accommodate their cyclopeptides. Molecular modeling by AutoDock Vina reveals that certain cyclopeptides in these plants have the potential for DPP4 inhibition. In particular, “Heterophyllin B” from P. heterophylla, “Cyclolinopeptide C” from flaxseed, and “Diandrine C” from D. diandra, with binding affinities of −10.4, −10.0, and −10.7 kcal/mol, are promising. Docking suggests that DPP4 inhibition may be one of the reasons why these three plants are beneficial for lowering blood sugar. Because many protein hydrolysates have shown the effect of DPP4 inhibition, a series of peptides derived from Heterophyllin B precursor “IFGGLPPP” were included in the study. It was observed that IFWPPP (−10.5 kcal/mol), IFGGWPPP (−11.4 kcal/mol), and IFGWPPP (−12.0 kcal/mol) showed good binding affinity and interaction for DPP4. Various IFGGLPPP derivatives have the potential to serve as scaffolds for the design of novel DPP4 inhibitors.